2010
DOI: 10.1136/bmj.c1642
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of screening for Chlamydia trachomatis to prevent pelvic inflammatory disease: the POPI (prevention of pelvic infection) trial

Abstract: Objective To determine whether screening and treating women for chlamydial infection reduces the incidence of pelvic inflammatory disease over the subsequent 12 months.Design Randomised controlled trial.Setting Common rooms, lecture theatres, and student bars at universities and further education colleges in London.Participants 2529 sexually active female students, mean age 21 years (range 16-27).Intervention Participants completed a questionnaire and provided self taken vaginal swabs, with follow-up after one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
346
0
20

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(376 citation statements)
references
References 21 publications
10
346
0
20
Order By: Relevance
“…In contrast, two randomized trials comparing chlamydia screening in young women with a control group not invited for testing found a 50% reduction in PID over the subsequent year (64,82). Finally, in another randomised trial, limited evidence was observed suggesting that screening for chlamydia reduces PID rates: 10% of asymptomatic infected women not treated developed PID within a year, versus 2% of screened and treated women (63). Further studies evaluating the effectiveness of chlamydia screening are clearly needed.…”
Section: Preventionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, two randomized trials comparing chlamydia screening in young women with a control group not invited for testing found a 50% reduction in PID over the subsequent year (64,82). Finally, in another randomised trial, limited evidence was observed suggesting that screening for chlamydia reduces PID rates: 10% of asymptomatic infected women not treated developed PID within a year, versus 2% of screened and treated women (63). Further studies evaluating the effectiveness of chlamydia screening are clearly needed.…”
Section: Preventionmentioning
confidence: 87%
“…However, the risk of developing PID among C. trachomatis-infected women is not well known since few prospective studies have been performed and the number of cases included has generally been small. Despite these limitations, the risk seems to be high: the results of a recent randomised controlled trial performed in the UK that included 75 women with untreated, asymptomatic C. trachomatis infection found that 9.5% (95% CI 4.7%-18.3%) developed PID over 1 year (63). Although current data are limited, the risk of developing PID seems to be higher in the first few weeks of infection (41).…”
Section: Main Reproductive Health Sequelae In Women 321 Pidmentioning
confidence: 99%
“…These authors conclude that their study shows that a longer duration of the asymptomatic period results in a more pronounced impact of a screening programme (Althaus et al, 2010). The incidence of PID in untreated women infected with C. trachomatis has been reviewed and widely discussed in the literature in terms of (1) its cost-effectiveness as a screening program and (2) as a predictor of tubal damage in infertile patients (Aghaizu et al, 2008;Althaus et al, 2010;Bakken & Ghaderi 2009;den Hartog et al, 2008;Dietrich et al, 2010;Kalwij et al, 2010;Land et al, 2010;Low et al, 2009;Low & Hocking 2010;Oakeshott et al, 2010;Risser & Risser 2007;Simms & Horner 2008). In a comprehensive study that evaluated all available original research and assessed the incidence of PID following C. trachomatis infection, it was concluded that no study could adequately answer the question and that many studies either had inaccuracies, validition problems or only indirect evidence to support their reported incidences (Risser and Risser, 2007).…”
Section: Chlamydia Screeningmentioning
confidence: 99%
“…The baseline prevalence of Chlamydia was 5.4% in the screened population of 2529 sexually active female students (mean age 20.9 years) and 5.9% in (deferred screening) controls with the incidences of PID found to be 1.3% and 1.9% respectively in these cohorts. It was reported that after 12 months, most episodes of PID occurred in women who tested negative for Chlamydia at baseline (9.5%) when compared to the intervention group (1.6%) and these authors concluded that the effectiveness of a single Chlamydia test in preventing PID over 12 months may also have been overestimated (Oakeshott et al, 2010). A Danish randomised trial was conducted with 9-year follow-up testing of 4000 asymptomatic women for the presence of urogenital Chlamydia trachomatis.…”
Section: Chlamydia Screeningmentioning
confidence: 99%
See 1 more Smart Citation